Needs assessment of the serious injuries following the September 1999 earthquake in Taiwan - Liao, Yen-Hsiung (International Journal of Health, 2013)
Purpose To investigate the basic and medical needs of 258 serious injuries in the Chi-Chi earthquake. Approach Subjects were collected from the Department of public Health Bureau, Nantou County Government. The participants were asked to complete the questionnaire about the basic and medical needs 5 months after the earthquake struck. Results There were 13 died, 8 still in hospital, and 250 discharged of the 271 serious injuries. Among the 250 discharged persons, 28 (11.2 %) needed home rehabilitation, 206 (82.4 %) needed hospital rehabilitation routinely, and 16 (6.4 %) cases were cured. The unemployment got the living fee less self-reliant than the employment (odds ratio = 214.67, 95 % confidence interval = 53.22 – 865.83). The unemployment needed the employment service more than the employment (odds ratio = 5.37, 95 % confidence interval = 1.20 – 23.94) also. There were no difference between the unemployment and employment for the needs of home rehabilitation, mental counseling, financial support, vocational training, and accommodation service. These analyses suggested that provides both the extent rehabilitation service and job service for the still unemployed as the major strategies for serious injuries in Taiwan.